Neonatal Hyperglycemia due to Transient Neonatal Diabetes Mellitus in Puerto Rico. (20th October 2015) - Fargas-Berríos, N.; García-Fragoso, L.; García-García, I.; Valcárcel, M.
Abstract : Neonatal hyperglycemia is a metabolic disorder found in the neonatal intensive care units. Neonatal diabetes mellitus (NDM) is a very uncommon cause of hyperglycemia in the newborn, occurring in 1 in every 400, 000 births. There are two subtypes of neonatal diabetes mellitus: permanent neonatal diabetes mellitus (PNDM) and transient neonatal diabetes mellitus (TNDM). We describe a term, small for gestational age, female neonate with transient neonatal diabetes mellitus who presented with poor feeding tolerance and vomiting associated with hyperglycemia (385 mg/dL), glycosuria, and metabolic acidosis within the first 12 hours of life. The neonate was treated with intravenous insulin, obtaining a slight control of hyperglycemia. An adequate glycemia was achieved at 5 weeks of life. The molecular studies showed complete loss of maternal methylation at the TND differentially methylated region on chromosome 6q24. The etiology of this neonate's hyperglycemia was a hypomethylation of the maternal TND locus. A rare cause of neonatal diabetes mellitus must be considered if a neonate presents refractory hyperglycemia. To our knowledge, this is the first case reported in Puerto Rico of transient neonatal mellitus due to the uncommon mechanism of maternal hypomethylation of the TND locus. Its prevalence in Puerto Rico is unknown.